Komunikasi Ko-Kreasional Program Sehat Sejahtera (SESERA) PT Pupuk Sriwidjaja dengan Masyarakat Pulau Kemaro - Rozalena, Agustin; Dyanrini, Alde (PT. Anagata Sembagi Education, 2024)
The purpose of this study is to investigate the co-creative communication of the Sehat Sejahtera Program (Sesera) and to construct a collaborative model between corporate and community in the context of implementing ecotourism at the Kemaro Island tourist attraction in Palembang City. This study uses qualitative methodologies and a case study design to handle primary data based on interviews, non-participant observation, and documentation as secondary data. The data analysis employs the Miles and Huberman Interactive Model in three steps, beginning with data reduction and structured in a relationship pattern to facilitate interpretation and drawing or verifying results. Research findings show that co-creational communication referring to Co-Creation Theory is implemented through social responsibility strategies focussing on tourist experiences and interactive relationships with the surrounding community. The collaboration carried out is PT Pupuk Sriwidjaja Palembang's social and environmental responsibility (TJSL) approach to the Kemaro Island tourist destination.